Age dependence of cracking and deformability of a strain-hardening cement-based composite. (30th July 2019) - Klink, Thomas; Stegmann, Florian; Slowik, Volker
Highlights: Strain-hardening cement-based composites (SHCC) have a large strain capacity. This strain capacity decreases with the age of initial loading. The tested material did still exhibit strain-hardening behavior after seven months. No systematic influence of the age on the crack width distribution was found. Abstract: Strain-hardening cement-based composites (SHCC) are characterized by numerous fine cracks being formed under tension and, consequently, by a high post-cracking deformability. The age dependence of this behavior was experimentally investigated for a cement-based mortar containing randomly distributed polyvinyl alcohol (PVA) fibers. Specimens made of this material were subjected to uniaxial tension. The age of initial loading varied from seven days to almost seven months. In addition to the stress-strain curves, the crack patterns were recorded and evaluated by optical methods. The first-cracking stress slightly increased and the strain at crack localization decreased with the material's age at initial loading. Despite the observed age effect, the material did still exhibit strain-hardening behavior after almost seven months. No systematic influence of the age on the crack width distribution was found.